Identification of Production Decline Factors using the LEAN DMAI Method - Ika Widya Ardhyani; Sherly Ardhya Garini; Fitri Suhartiningrum; Qurrota Akyun (Jurnal Ilmiah Teknik Industri, 2023)
PT Himalaya Mitra Sukses, is a company engaged in the cooking seasoning and flavoring industry. The products produced include tomato sauce, chili sauce, and premix flour. The company has problems achieving less than optimal productivity, which later became the basis of this research. In this research, identification of waste that occurs in the production process using the Lean DMAI method. The data in this research were processed and analyzed based on 4 main stages: (1) Big Picture Mapping (BPM); (2) making Pareto Diagrams; (3) Root Cause Analysis (RCA); (4) the Failure Mode Effect and Analysis (FMEA) method to reduce the existing waste. Based on the results of the research, it is known that the types of waste identified are overproduction, defects, waiting processes, unnecessary inventory, and excess displacement. Of these many factors, the largest waste is caused by the defect factor of the tomato sauce type product which is runny and too acidic, because the operator does not follow the existing SOP with an RPN value of 392.